Hardy type spaces on infinite dimensional group orbits - Oleksienko, M. V.; Lopushansky, O. V. (Methods of Functional Analysis and Topology, 2011)
In Hilbert Hardy spaces of complex analytic functions with infinitely many variables, defined on unitary orbits of locally compact second countable group, the Cauchy type integral formulas are established. Existence of radial boundary values is proved. Results are illustrated for a reduced Heisenberg group.